Expanding the Noonan spectrum/RASopathy NGS panel: Benefits of adding NF1 and SPRED1 - Leora Witkowski; Mitchell W. Dillon; Elissa Murphy; Matthew SLebo; Heather Mason‐Suares (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background RASopathies are a group of disorders caused by disruptions to the RAS‒MAPK pathway. Despite being in the same pathway, Neurofibromatosis Type 1 (NF1) and Legius syndrome (LS) typically present with phenotypes distinct from Noonan spectrum disorders (NSDs). However, some NF1/LS individuals also exhibit NSD phenotypes, often referred to as Neurofibromatosis‐Noonan syndrome (NFNS), and may be mistakenly evaluated for NSDs, delaying diagnosis, and affecting patient management. Methods A derivation cohort of 28 patients with a prior negative NSD panel and either NFNS or a suspicion of NSD and café‐au‐lait spots underwent NF1 and SPRED1 sequencing. To further determine the utility and burden of adding these genes, a validation cohort of 505 patients with a suspected RASopathy were tested on a 14‐gene RASopathy‐associated panel. Results In the derivation cohort, six (21%) patients had disease‐causing NF1 or SPRED1 variants. In the validation cohort, 11 (2%) patients had disease‐causing variants and 15 (3%) had variants of uncertain significance in NF1 or SPRED1. Of those with disease‐causing variants, 5/17 only had an NSD diagnosis. Conclusions Adding NF1 and SPRED1 to RASopathy panels can speed diagnosis and improve patient management, without significantly increasing the burden of inconclusive results.